Photo-electrochemical production of H2 using solar energy - Hankin,A; Kelsall,GH; Ong,CK; Petter,F (Chemical Engineering Transactions, 2014)
Ti | SnIV-Fe2O3 photo-anodes are implemented in a photo-electrochemical reactor for photo-assistedsplitting of water into hydrogen and oxygen. Attention is focused on the issues concerning electrode scaleupwith the aim of addressing the present need for the design, optimisation and demonstration of thecommercial feasibility of photo-electrochemical reactors.